ELECTRICAL RESISTIVITY BASED SHALLOW CRUSTAL DEFORMATION ANALYSIS IN AN ACTIVE SEISMIC ZONE - Gunjan Mukherjee; Chandrani Debbarma; Sushmita Paul; Sudip Dey (Faculty of Geography, Universitas Gadjah Mada, 2011)
This paper aims to assess the shallow crustal deformation in a highly seismic-prone zone ofnortheast India. For that purpose, Tripura University campus has been selected which isnearly 8 km away from Agartala city. The field work was conducted by using electricalresistivity meter. Vertical Electrical Sounding or VES method of resistivity survey wasadopted for measuring the electrical resistivity and structural analysis of the study area.Total four VES points were recorded namely near the Department of Physics, Department ofGeography and Disaster Management, Teachers’ Residential area and Girls’ Hostel. Therecorded data was measured and two different electrical profiles were drawn i.e. (a) Physicsbuilding to Geography buildings and (b) teachers’ quarters to Girls’ Hostel. From theelectrical resistivity profiles, a clear break in resistivity characters has been observed in thewestern part which is located near the Tripura University Girls’ Hostel. This clearly provesthat a deformation occurred in this area below 4 m depth and it can be very dangerous if ahigh magnitude seismic slip takes place. From this observation, this hostel is detected as themost risk prone building. Apart from that, the teachers’ quarters near the Girls’ hostel havealso been detected as equally risk prone. From this point of view it can be recommended thatconstruction of heavy buildings should be restricted in Tripura University campus as thesubsurface deformation zone can create faulting during high magnitude earthquake.